2023
DOI: 10.1186/s12984-023-01123-w
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a combined intermittent theta-burst stimulation and video game-based dexterity training in Parkinson’s disease

Abstract: Background Persons with Parkinson’s disease (PD) often exhibit difficulties with dexterity during the performance of activities of daily living (ADL), inter alia due to dysfunctional supplementary motor area (SMA). Combined intermittent theta-burst stimulation (iTBS) over the SMA followed by video game-based training (VBT) may therefore improve dexterity related ADL. The VBT may induce high flow levels related to high performance during the training. The aim of this study is to evaluate the fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A notable 46.67% (N = 21) of studies pinpointed regime intensity as a key determinant of adherence. Intensive and challenging programs can yield lower adherence in some people, especially if they induce pain or fatigue [22,35,45,59], but for others may optimize adherence [35,46,60,61]. Langer et al (2021) found that the inherent challenges of rock-climbing spurred adherence due to a perceived high level of intrinsic reward for some people [62].…”
Section: Program Design Factorsmentioning
confidence: 99%
“…A notable 46.67% (N = 21) of studies pinpointed regime intensity as a key determinant of adherence. Intensive and challenging programs can yield lower adherence in some people, especially if they induce pain or fatigue [22,35,45,59], but for others may optimize adherence [35,46,60,61]. Langer et al (2021) found that the inherent challenges of rock-climbing spurred adherence due to a perceived high level of intrinsic reward for some people [62].…”
Section: Program Design Factorsmentioning
confidence: 99%